0025 Assessment and estimates of exposure to synthetic amorphous silica at five German production plants. (23rd June 2014) - Morfeld, Peter; Taeger, Dirk; Mitura, Heike; Bosch, Axel; Nordone, Adrian; Vormberg, Reinhard; McCunney, Robert; Merget, Rolf
Abstract : Objectives: Synthetic amorphous silicas (SAS) are nanostructured polymorphs of silicon dioxide. We compared two different exposure assessments. Method: This study estimated cumulative exposure to inhalable SAS dust in 484 male workers from five German SAS producing plants. Two procedures (P1, P2) were applied. P1 was based on an expert assessment. P2 was a multiple exposure assessment (15 scenarios) anchored by a recent measurement series (1375 personal measurements of inhalable SAS dust concentration) and used expert assessments. Results: Cumulative exposure estimates for P1 averaged 56.9 mg/m 3 -years (range: 0.1 to 419); for a selected P2 scenario the mean was 31.8 mg/m 3 -years (range: 0.4 to 480), (p < 0.0001). Averages varied between the 15 P2-scenarios from 12.6 to 109.6 mg/m 3 -years. Different time trends for SAS concentrations were observed. Conclusions: Both approaches suffer from considerable uncertainties that need to be considered in the epidemiological morbidity study.